Maternal mortality in a tertiary care hospital: a 3-year retrospective study - K. M., Harish; N., Shwetha; N., Nalini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Systematic review to determine the epidemiological aspects and causes of maternal mortality there by exploring possibility of intervention and implementing Evidence-based health policies and programmes to prevent future maternal death. Aims and objectives of the study were to calculate the maternal mortality rate in our hospital, to assess the epidemiological aspects of maternal mortality, to assess the type of delay and causes of maternal mortality and to suggest ways to reduce the MMR. Methods: This is a 3-year retrospective study from January 2017 to December 2019 that will be conducted in the department of obstetrics and gynaecology, The Apollo medical college and District hospital, Chittoor a tertiary care teaching hospital situated in the southernmost part of Andhra Pradesh state in India. It gets a large number of referrals from PHCs, CHCs, and maternity homes as well as from hospitals across Chittoor district. Epidemiological data will be collected from the hospital register. Maternal mortality ratio, epidemiological factors and causes affecting maternal mortality are assessed. Results: MMR in present study was 66 per 1,00,000 live births. Women in the age group of 20 to 30 years (85.72%), illiteracy (57.16%) and low socioeconomic status (100%) were risk factors for maternal mortality. Obstetric haemorrhage (57.16%) is most common cause whereas type 1 and type 2 delays are most common contributing factors for maternal mortality. Conclusions: Early identification and management of pregnancy complication, strengthening of existing Emergency obstetric care (EmOC) facilities, easy transport and appropriate referral linkages are keys to reduce maternal mortality to further extent.